Normal saline instillation before suctioning: A meta-analysis of randomized controlled trials. Issue 5 (September 2017) - Wang, Chia-Hui; Tsai, Jui-Chen; Chen, Shu-Fen; Su, Chien-Ling; Chen, Lawrence; Lin, Chao-Chun; Tam, Ka-Wai
Abstract: Background: For airway management of intensive care unit (ICU) patients who are intubated, a 5–10-mL bolus of sterile normal saline (NS) solution is commonly instilled into an endotracheal or tracheostomy tube before suctioning. However, NS instillation has been associated with adverse events such as dyspnea, increasing heart rate, decreasing of oxygenation, blood pressure, and other vital parameters. Objective: To conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the necessity of NS instillation before suctioning in ICU patients. Data sources: The PubMed, Embase, Cochrane Library, and Scopus databases and theClinicalTrials.gov registry were searched for studies published before May 2016. Review methods: RCTs evaluating the outcome of NS instillation before suctioning in ICU patients undergoing endotracheal intubation or tracheostomy were included. Individual effect sizes were standardised, and a meta-analysis was conducted to calculate the pooled effect size by using a random-effect model. The primary outcome was the oxygen saturation immediately and 2 and 5 min after suctioning. The secondary outcomes were the heart rate and blood pressure after suctioning. Results: We reviewed 5 RCTs including 337 patients. Oxygen saturation was significantly higher in the non-NS group than in the NS group 5 min after suctioning. The pooled mean difference in oxygen saturation was −1.14 (95% confidence interval: −2.25 to −0.03). The heart rate and blood pressure did not differ significantly between the non-NS and NS groups. Conclusion: NS instillation before suctioning does not benefit patients undergoing endotracheal intubation or tracheostomy. Moreover, it reduces oxygen saturation 5 min after suction. However, our reviewed studies had a low methodological quality. Thus, additional studies involving large-scale RCTs are warranted.